2022
DOI: 10.1007/s11096-022-01381-z
|View full text |Cite
|
Sign up to set email alerts
|

The protected antimicrobial process in a University Teaching Hospital: a qualitative interview study exploring the knowledge, attitudes, and experiences of healthcare professionals

Abstract: Background The protected or restricted supply of certain antimicrobials such as linezolid, caspofungin, aztreonam, in the acute hospital setting is an important element of Antimicrobial Stewardship (AMS) programmes to address the growing problem of antimicrobial resistance. This process involves submitting an application for use to be reviewed typically by a Consultant Microbiologist, Infectious Disease Consultant or Antimicrobial Pharmacist. Aim To investigate healthcare professionals’ knowledge, experiences,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…According to a systematic review on the topic, this kind of protection and restriction system has the highest success rates (66–87%) and is at least three times more successful than persuasive practices in lowering costs, resistance issues, and the unnecessary use of antibiotics. 37 Remarkably, a recent meta-analysis found that antibiotic protection programs led to reductions in resistance rates, particularly for Pseudomonas species. 38 According to a different study, the rate of ESBL-producing Enterobacteriaceae family members other than Pseudomonas species dramatically dropped following the restriction of carbapenem-derived antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…According to a systematic review on the topic, this kind of protection and restriction system has the highest success rates (66–87%) and is at least three times more successful than persuasive practices in lowering costs, resistance issues, and the unnecessary use of antibiotics. 37 Remarkably, a recent meta-analysis found that antibiotic protection programs led to reductions in resistance rates, particularly for Pseudomonas species. 38 According to a different study, the rate of ESBL-producing Enterobacteriaceae family members other than Pseudomonas species dramatically dropped following the restriction of carbapenem-derived antibiotics.…”
Section: Discussionmentioning
confidence: 99%